BA 101B - Business Analytics - Mindy Bean (Linn-Benton Community College, 2018)
Second course in a two-course sequence. Introduces and applies technical skills around beginning and managing a small business, including spreadsheets and the use of charts and graphs. Includes reflection and discussion of the application of concepts to a real-world example. Requires teamwork and collaboration to be exercised in completing a group project. Covers application of financial, legal, and administrative procedures in running a business. Upon successful completion of this course, students will be able to: Represent business models in spreadsheets including preparation of charts and graphs. Apply key business activities and the primary concepts and terms associated with these activities. Manage a business interacting with the external environment (through a simulation) and describe how this interaction impacts both business and the external environment. Implement the financial, legal, and administrative procedures involved in starting new business ventures. Identify ethical issues facing businesses. Effectively collaborate with team members and communicate professionally.